A New Mutation in IDS Gene Causing Hunter Syndrome: A Case Report - Gomes, Caio Perez; Marins, Maryana Mara; Motta, Fabiana Louise; Kyosen, Sandra Obikawa; Curiati, Marco Antonio; D’Almeida, Vânia; Martins, Ana Maria; Pesquero, João Bosco (Frontiers in Genetics, 2020)
Rationale: Mucopolysaccharidosis type II (Hunter syndrome) is an X-linked multisystem disorder, caused by deficiency of the lysosomal enzyme iduronate-2-sulfatase (I2S). The clinical manifestations of this disease are severe skeletal deformities, airway obstruction, cardiomyopathy and neurologic deterioration. Patient: The patient is a 5y6m boy, with developmental delay, hearing loss, hepatosplenomegaly and skeletal dysplasia. He was diagnosed with mucopolysaccharidosis type II based on clinical manifestations, biochemical and genetic analysis. Outcomes: The patient carries a new mutation (c.879-1210_1007-218del) in hemizygosis in the IDS gene, which was defined as pathogenic according to the 2015 American College of Medical Genetics and Genomics-Association for Molecular Pathology guidelines and as responsible for the mucopolysaccharidosis type II phenotype in the patient.